2020
DOI: 10.1186/s12904-020-0531-5
|View full text |Cite
|
Sign up to set email alerts
|

Compassion fatigue, watching patients suffering and emotional display rules among hospice professionals: a daily diary study

Abstract: Background: Hospice workers are required to regularly use emotional regulation strategies in an attempt to encourage and sustain terminally ill patients and families. Daily emotional regulation in reaction to constantly watching suffering patients may be intensified among those hospice professionals who have high levels of compassion fatigue. The main object of this study was to examine the relationship between daily exposition to seeing patient suffering and daily emotional work, and to assess whether compass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 44 publications
1
12
0
2
Order By: Relevance
“…Specifically, our findings suggested that, the emotional involvement in reassuring patients who were distressed or upset for their health, as well as seeing patients dying without their families beside them (Daphna-Tekoah et al, 2020 ), had the potential to trigger trauma and thus increase the risk of developing intrusion symptoms. This is in line with previous studies that showed how exposure to patient-related stressful situations makes HCWs susceptible to PTS (Kerasiotis and Motta, 2004 ; Adriaenssens et al, 2012 ; de Wijn and van der Doef, 2020 ; Portoghese et al, 2020 ). Furthermore, our results confirmed that, during pandemics, HCWs are exposed to different kinds of job and emotional demands that may reduce their well-being and expose them to intrusion thoughts (PTS symptom) (Aghili and Arbabi, 2020 ; Blanco-Donoso et al, 2020 ; Cai et al, 2020 ; Chevance et al, 2020 ; Daphna-Tekoah et al, 2020 ; Pappa et al, 2020 ).…”
Section: Discussionsupporting
confidence: 91%
“…Specifically, our findings suggested that, the emotional involvement in reassuring patients who were distressed or upset for their health, as well as seeing patients dying without their families beside them (Daphna-Tekoah et al, 2020 ), had the potential to trigger trauma and thus increase the risk of developing intrusion symptoms. This is in line with previous studies that showed how exposure to patient-related stressful situations makes HCWs susceptible to PTS (Kerasiotis and Motta, 2004 ; Adriaenssens et al, 2012 ; de Wijn and van der Doef, 2020 ; Portoghese et al, 2020 ). Furthermore, our results confirmed that, during pandemics, HCWs are exposed to different kinds of job and emotional demands that may reduce their well-being and expose them to intrusion thoughts (PTS symptom) (Aghili and Arbabi, 2020 ; Blanco-Donoso et al, 2020 ; Cai et al, 2020 ; Chevance et al, 2020 ; Daphna-Tekoah et al, 2020 ; Pappa et al, 2020 ).…”
Section: Discussionsupporting
confidence: 91%
“…In addition, the important demands that nurses have to face during the pandemic usually add further emotional requests. Continuous exposure to patients' death and suffering can lead to vicarious trauma and secondary traumatic stress ( 12 , 45 ). Furthermore, our study shows that crying at work is associated with higher levels of job stress and rumination about the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“… 66 In this sense, to reduce ruminative thoughts about the pandemic, distraction techniques such as coping strategies may help HCWs to lessen job stress and recover after work. 65 Finally, we found that crying at work was strongly associated with job stress, rumination, and watching colleagues crying at work. Crying at work is more frequent when job stress is too high and physicians feel overwhelmed by excessive demands and emotional pressure.…”
Section: Discussionmentioning
confidence: 68%
“…For example, high exposure to patients’ death, patients’ suffering, and witnessing extreme physical pain in patients may result in emotional clashes, such as secondary traumatic stress. 64 , 65 Then, we considered ruminations about the pandemic and crying at work as HCWS health outcomes. Regarding rumination about the pandemic, we found that concerns about perceived impact on personal life were the main risk factor.…”
Section: Discussionmentioning
confidence: 99%